2020
DOI: 10.1371/journal.pone.0241563
|View full text |Cite
|
Sign up to set email alerts
|

The promise of an intersectoral network in enhancing the response to transgender survivors of sexual assault

Abstract: Objectives This study explores the promise of an intersectoral network in enhancing the response to transgender (trans) survivors of sexual assault. Methods One hundred and three representatives of healthcare and community organizations across Ontario, Canada were invited to participate in a survey. Respondents were asked to: 1) identify systemic challenges to supporting trans survivors, 2) determine barriers to collaborating across sectors, and 3) indicate how an intersectoral network might address these ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
(53 reference statements)
1
12
0
Order By: Relevance
“…In Nova Scotia, racialized women have reported feeling unwelcome and unheard in "mainstream" spaces for survivors of violence, including community-based services (Creating Communities of Care, n.d.). Our study also does not speak to the experiences of trans and nonbinary populations, who face both a greater risk of experiencing sexualized violence (Jaffray, 2020) and additional barriers to accessing services (Du Mont et al, 2020;Sualp et al, 2021). Future research should explore the service access experiences of diverse and marginalized populations.…”
Section: Strengths and Limitationsmentioning
confidence: 84%
“…In Nova Scotia, racialized women have reported feeling unwelcome and unheard in "mainstream" spaces for survivors of violence, including community-based services (Creating Communities of Care, n.d.). Our study also does not speak to the experiences of trans and nonbinary populations, who face both a greater risk of experiencing sexualized violence (Jaffray, 2020) and additional barriers to accessing services (Du Mont et al, 2020;Sualp et al, 2021). Future research should explore the service access experiences of diverse and marginalized populations.…”
Section: Strengths and Limitationsmentioning
confidence: 84%
“…This suggestion is helpful, as studies have indicated that repositories of online information can be a vital resource for trans persons, particularly youth. 17 In addition, establishing a membership directory of trans-affirming supports and services may improve referrals within and across regions 11 , 24 and could also facilitate direct access to safe, appropriate, and sensitive care for trans survivors. This could be particularly helpful where resources tend to be more scarce (e.g., in rural or northern communities).…”
Section: Discussionmentioning
confidence: 99%
“… 9 Based on these insights, a survey was distributed to all representatives to determine their priorities for specific Network activities and deliverables and solidify their status as Network members. 10 , 11 Survey results highlighted that, for a large majority of responding organizations (87.8%), the creation of a knowledge sharing portal to share organizational information, updates, research developments, and other resources was a priority. 10 This was an important finding as, to our knowledge, no other resource hub focused on trans-affirming care for sexual assault survivors has been available to service providers in this and other Canadian provinces.…”
Section: Introductionmentioning
confidence: 99%
“…Responding member organizations (64/93) represented a rich diversity of services including, but not limited to, counselling/mental health (77%), advocacy and outreach (67%), education and training (56%), healthcare (51%), sexual assault care (46%), and care for other forms of violence (42%) and varied in size from 100 or less employees (44%) to more than 1000 employees (16%). The input of diverse organizational representatives, of whom more than half had over a decade of experience in their role (53%) and a substantial minority were trans or gender diverse (26%) [ 23 ], was critical for further guiding the development of the network. For example, the highest prioritized deliverables–provision of standardized sensitivity training on violence against trans persons for professionals and development of an online directory/resource list of trans-affirming service providers and organizations–directly informed our next steps.…”
Section: Introductionmentioning
confidence: 99%